ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SEKOLAH DASAR PADA PEMBELAJARAN MATEMATIKA - Ira, Ira; Mastiah, Mastiah; Rudiansyah, Eko (STKIP Melawi, 2024)
Abstract: This research was motivated by the lack of critical thinking skills of fifth grade students at SD Negeri 12 Engkurai in mathematics learning. The aim of the research was to determine the results of the analysis of critical thinking skills of fifth grade elementary school students in mathematics learning at SD Negeri 12 Engkurai with the indicators of critical thinking skills used, namely interpretation, analysis, evaluation and inference. The method used is a qualitative method with a case study approach. The technique for determining subjects in this research used purposive sampling. The subjects in this research were fifth grade students, with high, medium and low categories grouped based on the results of critical thinking ability tests. The object of this research is the critical thinking ability of fifth grade students at SD Negeri 12 Engkurai. The data collection techniques in this research used tests, interviews and documentation. The research instrument uses test sheets, interview sheets, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Data validity using triangulation techniques. The results of the research show that the critical thinking skills of fifth grade students at SD Negeri 12 Engkurai in solving critical thinking ability test questions in mathematics learning, especially in fraction counting operations, are still relatively low, this is proven by the average score of the critical thinking ability test results for all class students. V SD Negeri 12 Engkurai is 45, the highest score is 62.5 in the medium level critical thinking ability category, and the lowest score is 25 in the low level critical thinking ability category.Keywords: Analysis, Ability, Critical ThinkingÂ Abstrak: Penelitian ini dilatarbelakangi kurangnya kemampuan berpikir kritis siswa kelas V SD Negeri 12 Engkurai pada pembelajaran matematika. Tujuan penelitian untuk mengetahui hasil analisis kemampuan berpikir kritis siswa kelas V sekolah dasar pada pembelajaran matematika di SD Negeri 12 Engkurai dengan indikator kemampuan berpikir kritis yang digunakan yaitu interpretasi, analisis, evaluasi, dan inferensi. Metode yang digunakan adalah metode kualitatif dengan pendekatan studi kasus. Teknik penentuan subjek dalam penelitian ini menggunakan purposive sampling. Subjek dalam penelitian ini adalah siswa kelas V, dengan kategori tinggi, sedang, dan rendah yang dikelompokkan berdasarkan hasil tes kemampuan berpikir kritis. Objek dalam penelitian ini kemampuan berpikir kritis siswa kelas V SD Negeri 12 Engkurai. Adapun teknik pengumpulan data dalam penelitian ini menggunakan tes, wawancara, serta dokumentasi. Instrumen penelitian menggunakan lembar tes, lembar wawancara, dan dokumentasi. Teknik analisis data meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data menggunakan triangulasi teknik. Hasil penelitian menunjukkan bahwa kemampuan berpikir kritis siswa kelas V SD Negeri 12 Engkurai dalam menyelesaikan soal tes kemampuan berpikir kritis pada pembelajaran matematika khususnya pada materi operasi hitung pecahan masih tergolong rendah, hal ini dibuktikan dengan skor rata-rata hasil tes kemampuan berpikir kritis seluruh siswa kelas V SD Negeri 12 Engkurai yaitu 45, skor tertingginya adalah 62,5 dengan kategori kemampuan berpikir kritis tingkat sedang, dan skor terendahnya adalah 25 dengan kategori kemampuan berpikir kritis tingkat rendah.Â Kata Kunci: Analisis, Kemampuan, Berpikir Kritis